Philosophy of Science: How to Identify the Potential Research for the Day after Tomorrow? - Søren Ventegodt; Joav Merrick (The Scientific World Journal)
We were asked to participate in a workshop to assist the European Commission on how to choose financial support for high-potential, basic research projects that can give new scientific breakthroughs and thus contribute significantly to the positive development of society, industry, and economy for the day after tomorrow. At this workshop, we analyzed the problem in some detail using experience from our own research on the global quality of life. We would suggest that the most promising projects have the following characteristics: (1) they are led by a brilliant researcher who considers his/her research to be “sweet science”, who wants to explain the anomalies of his/her field of science, and who lives in a nonmainstream scientific paradigm; (2) they are deeply engaged in the philosophical problems of their research field, they are searching eagerly for a new understanding and a new theory, giving new tools for measurement and creating change, and results are taken as feedback on all levels from tool to theory and philosophy; (3) they are focused on the key point(s), which is an essential feature of the universe that creates global change if intervened upon. At the NEST Pathfinder 2005 Topic Identification Workshop, Brussels 28 May 2004 entitled “Measuring the Impossible”, we advised the European Commission Research Directorate to allocate funds for projects focusing on the state of consciousness how to understand it, how to map it, and how to develop it.